Artificial Intelligence: Making crime easier in the world of finance? - Zulfikar Hasan; Diska Sendi Marisna (AL-ARBAH: Journal of Islamic Finance and Banking, 2024)
Purpose – This paper explores the dual role of artificial intelligence (AI) in the realm of finance, examining its potential to both enhance efficiency and exacerbate vulnerabilities to criminal activitiesMethod – The research methodology for this study focuses on exploring the relationship between artificial intelligence (AI) and its potential role in facilitating financial crimes. This section outlines the research design, data collection methods, data analysis techniques, and ethical considerationsResult – As AI technologies become increasingly integrated into financial systems, they offer unprecedented opportunities for streamlining operations, optimizing decision-making processes, and enhancing customer experiences. However, this digital transformation also presents new challenges, particularly in terms of security and fraud preventionImplication – By leveraging advanced algorithms and machine learning techniques, malicious actors may exploit AI-powered systems to perpetrate financial crimes with greater sophistication and scaleOriginality – This paper evaluates the implications of this evolving landscape, highlighting the need for robust regulatory frameworks, proactive risk management strategies, and ongoing collaboration between industry stakeholders and law enforcement agencies to mitigate the risks associated with AI-enabled financial crime